Development and psychometric validation of a novel patient survey to assess perceived quality of substance abuse treatment in South Africa - Myers-Franchi, Bronwyn; Govender, R.; Koch, J.R.; Manderscheid, R.; Johnson, K.; Parry, C.D.H. (2015)
Background: A hybrid performance measurement system that combines patient-reported outcome data with administrative data has been developed for South African substance abuse treatment services. This paper describes the development and psychometric validation of one component of this system, the South African Addiction Treatment Services Assessment (SAATSA).